(untitled) (Journal of Civil Engineering Researchers, 2023)
Nanotechnology is poised to offer a viable solution for achieving high performance in future construction projects. Among the innovative technologies being explored, smart concrete has garnered significant attention and undergone extensive research in reputable scientific centers worldwide in recent years. A notable advancement within this field is the development of self-healing concrete. Concrete structures are undeniably susceptible to cracking, primarily due to natural processes. These cracks serve as pathways for harmful substances to infiltrate and corrode the reinforcement bars, ultimately leading to the degradation of the concrete. Traditional approaches to address this issue involve the use of repair materials, particularly various polymers. However, these materials not only complicate the repair process but also have adverse environmental consequences. In light of these challenges, scientists have discovered an alternative method that involves incorporating bacteria into concrete production to create self-healing properties. This method not only reduces maintenance and repair costs but also minimizes environmental impact, thereby enhancing the durability and performance of the concrete while extending its service life. By harnessing the power of bacteria, self-healing concrete represents a significant breakthrough in sustainable construction practices.